Processing Tea Leaves as an Innovation in Traditional Soap Making in Gununglangit Village - Mulyanto, Arif; Maulidia, Qotrunnada; Dakhilullah, Ghozy Jiyad; Elviani, Desvitra; Andrio, Galang Kumara; Fatimaatuzahra, Hasna; Aqilla, Erpa Yasbil; Auliyah, Hilyatul; Ambi, Yuliana Rizka; Sasikirana, Inara; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This community service program was carried out in Gununglangit Village with the aim of enhancing local residents’ knowledge and skills in utilizing tea leaves as the main raw material for traditional soap production. The activity began with a presentation that covered general information about tea leaves, the benefits of using them for personal care products, the method of soap-making, specific formulations for tea leaf soap, and the step-by-step production process. Following the presentation, participants engaged in hands-on practice to produce tea leaf soap using prepared ingredients and equipment, guided closely by the facilitator team. The program results indicated a significant improvement in participants’ understanding of the health benefits of tea leaves, their antibacterial and antioxidant properties, as well as the technical aspects of making natural soap. The products created during the workshop demonstrated desirable qualities in terms of color, aroma, texture, and foaming ability. Furthermore, participants expressed interest in continuing production as a potential source of income, with tea leaf soap identified as a promising local specialty product. Discussions with village officials and community members also revealed a commitment to developing this innovation into a sustainable home industry. This initiative is expected to contribute positively to the local economy, promote environmentally friendly practices by reducing the use of synthetic soaps, and preserve the cultural heritage of traditional craftsmanship in Gununglangit Village